Pengaruh Fitur Cashback dan Promo Shopeepay Terhadap Pengelolaan Keuangan Mahasiswa Akuntansi Universitas Buana Perjuangan Karawang Angkatan 2022 - Amanda Augustine; Ujang Suherman; Thomas Nadeak (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to determine the effects of ShopeePay's cashback and promo features on the financial management of UBP Karawang Accounting students in the class of 2022, both partially and simultaneously, in the context of digital wallets. Using a descriptive-verification quantitative approach with a sample of 122 students (purposive sampling) and multiple linear regression, the results confirm that cashback has a positive and significant partial effect, as do ShopeePay promotions. Simultaneously, both are significant with F hit. 469.025 > F tab 3.071 and R² 0.887, meaning that 88.7% of the variation in financial management can be explained by these two variables. These findings conclude that students' financial management is significantly influenced by the intensity of cashback and ShopeePay promo utilization, so that these digital incentives not only trigger consumption but are also related to how students manage and control their personal finances. This study contributes to the development of personal financial management and behavioral finance literature in the context of digital wallets and serves as a basis for designing digital financial literacy programs in higher education institutions to guide the wiser use of digital incentives.